2019
DOI: 10.21470/1678-9741-2018-0352
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Aspects of No-Touch Saphenous Vein Graft Harvesting in CABG: Clinical and Angiographic Follow-Up at 3 Months

Abstract: With more than 800,000 coronary artery bypass grafting (CABG) operations annually worldwide and the saphenous vein being the most common conduit used, there is no question that improving saphenous vein graft patency is one of the most important tasks in CABG. This video describes the no-touch harvesting procedure of the saphenous vein on an 80-year old man with hypertension, hyperlipidemia and a previous myocardial infarction with percutaneous coronary intervention to the right coronary artery. He was complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Over two decades ago, the 'no-touch' (NT) technique of harvesting SV was introduced [13] . Using an atraumatic method, the vein is removed with a pedicle of surrounding tissue and with minimal vascular damage [14] . Subsequently, a randomized trial comparing C SVG and NT SVG has shown that the latter is superior in terms of patency rates and left ventricular ejection fraction at 1.5, 8.5, and 16 years postoperatively [15][16][17][18] , as seen in Table 1 from Samano et al [17] , 2015.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 99%
“…Over two decades ago, the 'no-touch' (NT) technique of harvesting SV was introduced [13] . Using an atraumatic method, the vein is removed with a pedicle of surrounding tissue and with minimal vascular damage [14] . Subsequently, a randomized trial comparing C SVG and NT SVG has shown that the latter is superior in terms of patency rates and left ventricular ejection fraction at 1.5, 8.5, and 16 years postoperatively [15][16][17][18] , as seen in Table 1 from Samano et al [17] , 2015.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 99%
“…Avoiding direct contact with the vessel prevents spasm and the need for manual distension. 25 Side-branches are ligated and divided at the same distance from the SV. After removal, the SV is stored in heparinized blood.…”
Section: No-touch Saphenous Vein Graft Harvestingmentioning
confidence: 99%
“…Hence, there is no need for distension and endothelial damage is minimized. 25 , 26 , 37 39 An additional beneficial effect of preserved outer layers of the SV is the protection conferred on the luminal endothelium once inserted as a graft and subjected to arterial hemodynamics. A study comparing sections of CT versus NT harvested SVs showed marked differences in endothelial integrity.…”
Section: Comparison Of Synthetic and Natural External Stents; Mechanical Propertiesmentioning
confidence: 99%
“…No results have yet been reported regarding PCI of a saphenous vein harvested with the no-touch (NT) [ 14 ] technique or treated in any other way during the primary CABG operation. The no-touch technique differs from the conventional (C) technique in that it causes less endothelium damage during the harvesting procedure [ 15 - 17 ] , and leads to reduced neo-intimal hyperplasia and subsequent atherosclerosis in the long term [ 18 - 20 ] . Our group has previously investigated HRQoL in CABG patients who had received a no-touch vein graft [ 11 ] , but that study did not compare the no-touch technique with the conventional technique.…”
Section: Introductionmentioning
confidence: 99%